Cross-modal facilitation of auditory discrimination in a frog. (29th June 2022) - James, Logan S.; Baier, A. Leonie; Page, Rachel A.; Clements, Paul; Hunter, Kimberly L.; Taylor, Ryan C.; Ryan, Michael J.
Abstract : Stimulation in one sensory modality can affect perception in a separate modality, resulting in diverse effects including illusions in humans. This can also result in cross-modal facilitation, a process where sensory performance in one modality is improved by stimulation in another modality. For instance, a simple sound can improve performance in a visual task in both humans and cats. However, the range of contexts and underlying mechanisms that evoke such facilitation effects remain poorly understood. Here, we demonstrated cross-modal stimulation in wild-caught túngara frogs, a species with well-studied acoustic preferences in females. We first identified that a combined visual and seismic cue (vocal sac movement and water ripple) was behaviourally relevant for females choosing between two courtship calls in a phonotaxis assay. We then found that this combined cross-modal stimulus rescued a species-typical acoustic preference in the presence of background noise that otherwise abolished the preference. These results highlight how cross-modal stimulation can prime attention in receivers to improve performance during decision-making. With this, we provide the foundation for future work uncovering the processes and conditions that promote cross-modal facilitation effects.